Expressão gênica da prolactina, do receptor de prolactina e das hialuronam síntases e a imunoistoquímica do ácido hialurônico e do receptor CD44 em úteros de camundongos fêmeas com hiperprolactinemia induzida pela metoclopramida, durante as fases do ciclo estral - Gomes, Regina Célia Teixeira [UNIFESP] (2011)
OBJECTIVE: To evaluate the gene expression of prolactin, prolactin receptor and hialuronan sintase and immunohistochemistry of hyaluronic acid and CD44 in the uterus of female mice with metoclopramide-induced hyperprolactinemia throughout the estrous cycle. METHODS: 80 adult (100 days old) female virgin mice were randomly divided into two groups of 40 animals each: control (Ctr), which received intraperitoeneal (IP) 0.2 ml of saline solution, and so labeled hyperprolactinemic (HPrl), which received IP 6,7 ìg/day metoclopramide. After 50 days the animals were properly randomly divided into 8 groups of 10 animals, according to the phase of the cycle: proestrus (Ctr and HPrl), estrus (Ctr and HPrl), metaestrus (Ctr and HPrl) and diestrus (Ctr and HPrl). Under deep anesthesia, a part of the middle portions of the uterine horns were removed for detection of genes by PCR Real Time methods. Another part was fixed in 10% formol for immunohistochemical evaluation of HA, HAS1, 2 e 3 distribution and CD44. The results were submitted statistical analysis. RESULTS: Comparing the experimental group with the control group results were compared immunohistochemistry: hyaluronic acid (HA), the hyaluronic acid receptor (CD44) and hyaluronic synthases (HAS): hyaluronic acid’s immunopositivity in the extracellular matrix was higher in the estrus phase and decreased in metaestrus phase and increased the number of cells immunopositive for CD44 receptor during proestrus phase, metaestrus phase and diestrus phase. Also, increased the number of cells immunopositive for hyaluronic synthases HAS1 and HAS2 in proestrus phase, estrus phase and metaestrus phase. And decreased Has3 in proestrus phase and increased during estrus and metaestrus phase. The decreased gene expression of prolactin in proestrus phase and increased in diestrus phase. And the gene expression of prolactin receptor decreased during the proestrus and metaestrus phase and increased during estrus phase. Gene expression of the hyaluronic synthesis Has1 showed increased in proestrus phase and estrus phase. The gene expression of the Has2 has3 was low. Conclusion: Our data suggest that metoclopramide-induced hyperprolactinemia promotes structural and molecular changes in the uterus of female mice.